(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The present paper is a part of ongoing research of the authors in integrating Philosophy into managerial practices for creating virtuous employee engagement and organizational excellence. With the changing scenario and typical work styles, philosophy has a significant role in creating positive leadership who practices compassion, love, and truth for creating inclusive organizations. In this paper, the authors have aimed to give a background of the relevance of Quakers philosophy to managerial practices by citing examples through the specific case of Cadbury Schweppes and other brief reflections across the globe. The current article claims a great deal to be learned about business practices by reflecting on how the Friends, mostly forgotten and disregarded in the foundation narratives of management studies, were structured and how they successfully managed their businesses. The authors also consider multiple implications that management studies may derive from researching the Quakers’ management style in the future. Consequently, the authors suggest that now would be the wise moment to reclaim truthfulness and behave ethically and constructively.